2016
DOI: 10.1039/c6ra01023g
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state polymerization of EDTA and ethylenediamine as one-step approach to monodisperse hyperbranched polyamides

Abstract: Hyperbranched polyamides (HBPAs), a special class of polymers with extended use in colloidal systems, is synthesized by an innovative method taking advantage of the ordered aggregation of positive and negative molecular ions in solid-state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Based on the chemical structure, the EDTA has four symmetrical carboxyl groups, which could react with the hydroxy group to form an ester bond. Copolymerizing with EDTA as a cross-linking agent can form network polymers to increase the toughness and elasticity of copolymers [54]. These kinds of network structures play a role in improving the thermal stability and mechanical strength of copolymers [55].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the chemical structure, the EDTA has four symmetrical carboxyl groups, which could react with the hydroxy group to form an ester bond. Copolymerizing with EDTA as a cross-linking agent can form network polymers to increase the toughness and elasticity of copolymers [54]. These kinds of network structures play a role in improving the thermal stability and mechanical strength of copolymers [55].…”
Section: Introductionmentioning
confidence: 99%
“…The solid-state synthesis method used in this study is inspired by the work of Tomaz et al, 26 where a solid-state reaction between an organic acid and an amine is shown. In their interesting study, they took advantage of oriented conjugate salts with a certain order, produced by the neutralization reaction between ethylenediamine tetraacetic acid (EDTA) and EDA at different ratios and solvent evaporation.…”
Section: Resultsmentioning
confidence: 99%
“…Ethylenediaminetetraacetic acid (EDTA) is widely utilized as a chelating agent for the removal of metal ions, adhesives, and antioxidants, as well as in bioengineering and other fields. , The chemical structure of EDTA has two nitrogen atoms in the center and four symmetrical −COOH groups, which react with the −OH group to produce an ester bond. The toughness and elasticity of copolyesters can be reinforced by copolymerizing with EDTA as a cross-linking agent to form a network architecture, which plays a role in improving the thermal stability and mechanical strength of copolyesters . As described above, the aliphatic polyester can form a three-dimensional (3D) network architecture through copolymerization with tetra-functional cross-linking agents such as ethylenediaminetetraacetic acid, which have been recognized in a strictly controlled content to explore the thermal and mechanical properties and the crystallization behavior in our research …”
Section: Introductionmentioning
confidence: 99%